Pengaruh Pembiayaan qard Al-Hasan BWM Alpen Barokah Mandiri terhadap Peningkatan Perekonomian Masyarakat Pragaan Sumenep - Kholilur Rahman; Khotamar Rosid (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aims to determine whether there is an effect of financing qard{ al-h{asan BWM Alpen Barokah Mandiri on improving the economy of the community Pragaan Sumenep. to know how much the influence of qard{ al-h{asan financing on the community's economy. This study aims to determine whether there is an effect of financing qard{ al-h{asan BWM Alpen Barokah Mandiri on improving the economy of the community Pragaan Sumenep. to know how much the influence of qard{ al-h{asan financing on the community's economy. This research uses a quantitative approach with simple linear regression analysis techniques. The type of data used is primary data obtained through distributing questionnaires. The sample of this study were 138 customers. The results of the study show that qard{ al-h{asan BWM Alpen Barokah Mandiri has a positive and significant effect on Employee Performance improving the economy of the community.